2010
DOI: 10.3390/molecules15117825
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Antimicrobial Activities of Lippia multiflora Moldenke, Mentha x piperita L. and Ocimum basilicum L. Essential Oils and Their Major Monoterpene Alcohols Alone and in Combination

Abstract: Essential oils from leaves of Lippia multiflora, Mentha x piperita and Ocimum basilicum from Burkina Faso were analysed by GC–FID and GC–MS. Major components were p-cymene, thymol, β-caryophyllene, carvacrol and carvone for L. multiflora, menthol and iso-menthone for M. x piperita and, linalool and eugenol for O. basilicum. The essential oils and their major monoterpene alcohols were tested against nine bacterial strains using the disc diffusion and broth microdilution methods. The essential oils with high phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
161
1
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(183 citation statements)
references
References 31 publications
11
161
1
10
Order By: Relevance
“…Pascual et al (2001) extensively revised the chemistry of Lippia and found that the components with the highest frequency in the essential oils of this genus are limonene, b-caryophyllene, p-cymene, camphor, linalool, a-pinene, and thymol. Furthermore, the sesquiterpene b-caryophyllene present in L. thymoides also appears as the main compound in other species at 11% in Lippia americana2 (Bueno et al, 2011), 15-16% in L. graveolens (Rivero-Cruz et al, 2011, 13% in Lippia multiflora Moldenke (Bassolé et al, 2010), and 18% in L. dulcis (Moreno-Murillo et al, 2010). Minor compounds present in the essential oils from L. thymoides are also in other species of the same genus, as camphor at 33% in L. dulcis (Görnemann et al, 2008), borneol at 9% in Lippia integrifolia Griseb.…”
Section: Discussionmentioning
confidence: 99%
“…Pascual et al (2001) extensively revised the chemistry of Lippia and found that the components with the highest frequency in the essential oils of this genus are limonene, b-caryophyllene, p-cymene, camphor, linalool, a-pinene, and thymol. Furthermore, the sesquiterpene b-caryophyllene present in L. thymoides also appears as the main compound in other species at 11% in Lippia americana2 (Bueno et al, 2011), 15-16% in L. graveolens (Rivero-Cruz et al, 2011, 13% in Lippia multiflora Moldenke (Bassolé et al, 2010), and 18% in L. dulcis (Moreno-Murillo et al, 2010). Minor compounds present in the essential oils from L. thymoides are also in other species of the same genus, as camphor at 33% in L. dulcis (Görnemann et al, 2008), borneol at 9% in Lippia integrifolia Griseb.…”
Section: Discussionmentioning
confidence: 99%
“…This increase of efficacy could be attributed to synergism or addition effect of antibacterial compounds of the EOs combined. Some study has reported that mixture of EOs showed interaction activity with each other acting as additive, synergistic and in a few cases antagonistic agents (Gutierrez et al, 2009;Bassolé et al, 2010;Bassolé et al, 2011). The restriction of combined EOs activities to Salmonella typhimurium and Salmonella paratyphimurium and its recurrent bactericidal activities to same strains sensitive to Cymbopogon citratus can be due to the fact that the whole combination activity may be influenced by the presence of Cymbopogon citratus EO for each one.…”
Section: Antibacterial Activity Of Essential Oils In Combinationmentioning
confidence: 99%
“…It has been explained that essential oils combination has the advantage to have the effect at many sites of action on bacterial cells with several mechanisms of action. It therefore result an increase of the effect and a limitation of the phenomenon of resistance (Bassolé et al, 2010;Bassolé et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…On remarque essaiment que l'huile la plus efficace (O. brasilicum) contient majoritairement du méthyl-chavicol (85,92%), qui serait le principal composé antimicrobien de cette huile. La forte activité antimicrobienne de cette huile essentielle avait été aussi constatée par Bassolé et al (2010). En effet, le Méthyl-chavicol, appelé aussi couramment l'Estragol, fait partie de la famille des méthyl-éthers.…”
Section: Discussionunclassified